Development of Discovery Learning Based Physics Learning Module in Energy Discussion - Suci Awaliyah Rizky; Neng Nenden Mulyaningsih; Yoga Budi Bhakti (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2021)
Learning physics on the subject of energy still seems difficult for students. To overcome this problem, teaching materials that can clearly explain physics concepts such as modules were needed. The purpose of this research was to develop a physics learning module that is suitable as teaching material referring to the expert validator's assessment. The research method used was the research and development method with the development process using the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The data collection instrument consisted of material expert validation sheets, media experts and linguists. The results of the study obtained the percentage of the validation value of 83.86% with a good category. Based on the research results, it can be concluded that the physics learning module based on discovery learning on the subject of energy was valid to be used as an alternative teaching material in physics learning.